Feasibility of Using the International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY) as a Framework for Aquatic Activities: A Scoping Review - Merav Hadar-Frumer; Huib Ten-Napel; Maria José Yuste-Sánchez; Isabel Rodríguez-Costa (MDPI AG, 2023)
(1) Background: In recent years, reviewing studies of aquatic activities for children with developmental delays has been a complex task due to the multitude of indices and professional languages. (2) Aim: To determine if the ICF-CY framework can be used as the unifying language in AA studies of children with DD. (3) Methods: Part One-A systematic review of selected studies focusing on goals that were found to be positive. These goals were linked to the ICF-CY categories. Part Two-Review of all studies using the ICF-CY's functioning components. (4) Results: Most of the positive goals were properly linked to ICF-CY and made it possible to review the 71 articles in a uniform language. (5) Conclusions: It is feasible to use the ICF framework as a universal structure and language.